Byzantine painting from the second half of the 10th to early 11th century in manuscript illumination - Zakharova, Anna V. (Actual Problems of Theory and History of Art, 2012)
The article gives an outline of the stylistic development of Byzantine painting from the classicizing art of the Macedonian renaissance to the so called “ascetic trend”, which dominated in the 1030–1040s. As far as too few works of monumental and icon painting dating to the second half of the 10th – early 11th c. survive, it is book illumination that gives the possibility to trace some most important processes in Byzantine art of this period.
Keywords: Byzantine painting; book illumination; miniature; Macedonian Renaissance; ascetic trend; Trebizond Lectionary; Menologium of Basil II; Dovolja Gospels